Comparative Analysis Of The Financial Performance Of Islamic Banks And Conventional Banks During The Covid-19 Pandemic - Novi Aditya; Nana Diana (Peneliti.net, 2023)
This study aims to analyze the comparison of the impact of the Covid-29 pandemic on the financial performance of Islamic and conventional banks in Indonesia where the financial performance ratio used is sourced from banking statistics which include: CAR and ROA, in 2019-2021. This study used one of the Islamic and conventional banks that are included in the BUKU III category as a research sample. This study uses a descriptive approach with a sample of Islamic and conventional banks that have been determined. The data taken is secondary data in the form of data in the financial statements at the bank. Base on the result previously obtained, it can be concluded that the financial perfomance of Islamic and Conventional banks based on capital adequency indicators (CAR) has not been distrupted by the Covid-19 pandemic, as evidenced by the perfomance of two banks which still show positive growth. And from the Ratio On Asset Indicators it can be concluded that although the ROA performance at Bank BNI is superior to Bank Muamalat. Bank BNI feelss a greater negative impact than Bank Muamalat as evidenced by a decreasse in the value of its ROA which is greater thank Bank Muamalat.